KOMUNIKASI DALAM MEMBENTUK IKLIM ORGANISASI DI LINGKUNGAN KAMPUS UNIVERSITAS ISLAM NEGERI (UIN) AR-RANIRY BANDA ACEH - Heri Rahmatsyah Putra (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2020)
The study aims to determine the organizational communication process between lecturers and staff in shaping the organizational climate as an effort to increase student satisfaction at the Ar-Raniry State Islamic University in Banda Aceh. In conducting this research, researchers used a qualitative approach using interview techniques with several members of the organization namely lecturers, employees, and students. Researchers also made direct observations at five faculties at UIN Ar-Raniry. From the results of the research conducted showed that the organizational communication process that has been going on between lecturers, staff, and students is still not running effectively. This is due to miscommunication that occurs as well as unsatisfactory employee service performance. The tight schedule of several lecturers is also a problem in increasing student satisfaction. Organizational communication that occurs linearly, top down, even circularly has not yet been formed as a whole and effectively. This then forms a closed organizational climate. The closed climate of organizational communication has been a limiting factor for the communication of lecturers and staff in increasing the satisfaction of UIN Ar-Raniry students.